Distribution of Fluvoxamine and Identification of the Main Metabolite in a Fatal Intoxication. Issue 4 (2nd July 2020) - Vignali, Claudia; Moretti, Matteo; Quaiotti, Jessica; Freni, Francesca; Tajana, Luca; Osculati, Antonio Marco Maria; Morini, Luca
Abstract: Fluvoxamine is a selective serotonin reuptake inhibitor, with a half-life of about 30 hours, that is commonly prescribed in the treatment of depression and obsessive and compulsive disorders. Though its more favorable adverse effect profile in comparison to tricyclic antidepressants, overdosages could lead to severe central nervous system depression. We hereby report the case of a 48-year-old woman with psychiatric disorders, who died in the Protected Community where she lived. An autopsy, during which multiorgan congestion and aspiration of gastric content were found, was performed 9 days after the death. Femoral and cardiac blood, urine and bile were collected for toxicological analysis. GC–MS, LC–MS-MS and LC–HRMS screenings were performed on blood samples. The analysis allowed to identify the following drugs: fluvoxamine, clotiapine, 7-aminoclonazepam, propranolol, gabapentin and haloperidol. Quantification of the detected drugs in blood was performed by means of a validated LC–MS-MS analytical procedure, and the following results were achieved: fluvoxamine (2.20 mg/L), gabapentin (41.00 mg/L), 7-aminoclonazepam (0.24 mg/L), clotiapine (0.07 mg/L), haloperidol (<0.01 mg/L) and propranolol (0.24 mg/L). Fluvoxamine concentration in blood exceeded 10 times the upper limit of therapeutic blood levels (0.23 mg/L). Contributory causes of death, such as due to multiple drug use, however, cannot be excluded. The distribution of fluvoxamine in all biological fluids was evaluated and a postmortem redistribution effect was observed (C/P blood ratio: 1.86). Fluvoxamine acid metabolite was identified in urine, bile and in cardiac blood, through an LC–QTOF analytical procedure.